Knowledge, attitude, and practice of human immune-deficiency virus (HIV) post-exposure prophylaxis among healthcare workers of governmental hospitals in Addis Ababa, Ethiopia - Ousman Adal; Asmamaw Abebe; Teshome Ayele (Elsevier, 2023)
Summary: Objectives: This study aimed to investigate the knowledge, attitude, and practice of human immunodeficiency virus (HIV) post-exposure prophylaxis (PEP) among healthcare workers in government hospitals in Addis Ababa, Ethiopia. Methods: A multicenter, cross-sectional study was conducted from March to April 2022. The lottery method of a simple random sampling technique was used to select six government hospitals. Structured, self-administered questionnaires were used to collect the data, which was coded into Microsoft Excel® and then exported to statistical package for social sciences (SPSS) ®Version 26 for further statistical analysis. Results: A large proportion of respondents (51.6%) and 63.6%) reported poor knowledge and practice respectively, regarding PEP for HIV. However, more than half of respondents (54.2%) had a favorable attitude toward PEP for HIV. Conclusion: A significant proportion of respondents had poor knowledge and practice regarding PEP for HIV, even though they had relatively favorable attitudes. Most healthcare workers (68.9%) did not receive any PEP training.